PERAN MAHKAMAH KONSTITUSI SEBAGAI PENJAGA KONSTITUSI: ANALISIS KRITIS TERHADAP KONSTITUSIONALISME DI INDONESIA - Zainal Abidin Pakpahan; Indra Kumalasari M (Jurnal Ilmiah Advokasi, 2025)
The Constitutional Court constitutes a key institution within Indonesia’s post-reform constitutional system, designed to uphold the supremacy of the Constitution and to strengthen constitutionalism in a democratic rule-of-law state. This article aims to critically examine the role of the Constitutional Court as the guardian of the constitution in the context of the development of constitutionalism in Indonesia, as well as to identify the juridical and institutional challenges faced in the exercise of this role. This study employs a normative legal research method using a statutory approach and a conceptual approach. The findings indicate that the Constitutional Court plays a strategic role in safeguarding the Constitution through its authority to conduct judicial review of legislation against the 1945 Constitution, resolve disputes concerning the powers of state institutions, dissolve political parties, and adjudicate disputes over general election results. Nevertheless, the practice of exercising these powers reveals a number of constitutional issues, including inconsistencies in judicial decisions, an increasing tendency toward judicial activism, and potential political pressures that may affect the Court’s legitimacy and independence. These conditions demonstrate that the role of the Constitutional Court as the guardian of the Constitution depends not only on its normative authority, but also on the consistency of constitutional interpretation and the strengthening of constitutional ethics in order to maintain a balance between constitutional supremacy and democratic principles. Keywords: Constitutional Court; Guardian of the Constitution; Constitutionalism; Rule of Law; Indonesia